Cross-sectional and longitudinal analyses of the effects of aging on memory in healthy young, middle-aged, and oldest-old adults : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Lamont, Allison (Massey University, 2006)
While a growing body of research indicates that older adults typically perform more poorly on many types of memory tasks than do younger adults, relatively little research has addressed the question of whether this trend continues unchanged into the late ninth and tenth decades of life. Such decrements in memory have been reported as linear declines from early adulthood up until about 80 years of age. Questions arise as to whether such memory declines slow or accelerate in very advanced aging, and to what extent differences are due to aging, per se, or variables that intervene between age and memory.To address these two questions, six memory types - verbal recall, nonverbal recall, short-term memory, working memory, face recognition, and prospective memory - were examined using both cross-sectional and longitudinal methodologies. The six types of memory and the influence of verbal processing speed, nonverbal processing speed, and intelligence were examined in mixed-gender groups of 20 - 40 (n = 40, M = 30.7, SD = 5.52), 50 - 70 (n = 44, M = 59.2, SD = 4.94), and 85+ year olds (n = 42, M = 87.8, SD = 2.43), at two points, the second occurring two years after the first. Each participant completed tests of word recall, geometric shapes recall, short-term memory (digit span), working memory (letter-number sequencing), face recognition, and prospective memory. Additionally, there were two processing speed tasks (Identical Pictures and Finding As), and the National Adult Reading Test of verbal fluency was used to estimate intelligence. The Mini-Mental State Examination and the Beck Depression Inventory (BDI-II) were used to screen for dementia and depression, respectively.At Time 1 testing the 85+ participants showed declines in all memory types (compared to the 20 - 40 year olds). Nonverbal recall (66.2% lower than the young group), working memory (46.2%), verbal recall (45%), and prospective memory (38.2%) produced the largest differences, short-term memory (12.3%) and face recognition (14.7%) the least. Two years later, the 85+ years old participants had shown further declines, relative to the 20 - 40 years group. Nonverbal recall (72.3% lower than the young group), prospective memory (63.2%), working memory (55.3%), and verbal recall (54.7%) continued to produce the largest decrements, with short-term memory (18.9%) and face recognition (19.8%) the least. The results for the young and middle participants did not change appreciably between Time 1 and Time 2. The difference between unadjusted scores and scores adjusted for intelligence, verbal processing speed, and nonverbal processing speed, increased markedly between Time 1 and Time 2 testing for the oldest-old participants.These findings support the view that while memory declines may be approximately linear from age 20 to 80 years, there is a sharp decline in most types of memory after the age of 85 years, recall and working memory suffering the most. Intelligence and processing speed have an effect on some types of memory, but age is by far the largest contributor to memory decline. Furthermore, as expected, all memory types declined over the two-year period, with prospective memory, verbal recall, nonverbal recall, and working memory showing the greatest declines. Short-term memory and face recognition declined at a noticeably slower rate.
Keywords: Effects of aging; Short-term memory; Working memory; Face recognition; Memory; Cognitive psychology; 380106 Developmental psychology and ageing